2019
DOI: 10.1029/2019wr025952
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Spaces of Long‐Term Catchment Water Balance

Abstract: Land and water management often relies upon relationships describing the catchment-scale water balance using only a few parameters. The classic Budyko and Turc frameworks are examples of these relationships applicable to large catchments, where the effect of climatic variables on the water balance overshadows that of catchment characteristics, including the catchment ability to store water to supply evapotranspiration. To account for the latter in the list of variables driving evapotranspiration, here we intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
(84 reference statements)
1
25
0
Order By: Relevance
“…Since each of the fluxes (L/T=Φ) can be used as a repeating variable, three hydrologic spaces are obtained. Assuming further that φ is a flux related to the storage capacity and the frequency of rainfall, φ = λw 0 , the three spaces (Daly et al, 2019) are found to coincide with specific cases in ( 19): case 1 if R is chosen as repeating variable, case 2 if ET max is chosen, and case 4 when φ is chosen.…”
Section: Storage Index: the Role Of The Hydrologic Active Depth And The Variability Timescalementioning
confidence: 83%
See 3 more Smart Citations
“…Since each of the fluxes (L/T=Φ) can be used as a repeating variable, three hydrologic spaces are obtained. Assuming further that φ is a flux related to the storage capacity and the frequency of rainfall, φ = λw 0 , the three spaces (Daly et al, 2019) are found to coincide with specific cases in ( 19): case 1 if R is chosen as repeating variable, case 2 if ET max is chosen, and case 4 when φ is chosen.…”
Section: Storage Index: the Role Of The Hydrologic Active Depth And The Variability Timescalementioning
confidence: 83%
“…While they did not use dimensional analysis, Turc and Budyko started their work by making what is perhaps the simplest hypothesis of a physical law for the rainfall partitioning (see Dooge, 1992;Daly et al, 2019, and references therein),…”
Section: Turc and Budyko Spaces: Dryness And Humidity As Main Controls Of Rainfall Partitioningmentioning
confidence: 99%
See 2 more Smart Citations
“…) can be manipulated into a single-parameterBudyko equation (e.g., Harman et al (2011);Daly et al (2019b)). There are likely many more, all equally valid, versions with even starker differences in the shapes of the curves (leading to even larger discrepancies between formulations if the current interpretations of explicit Budyko curves and parametric Budyko equations are maintained).…”
mentioning
confidence: 99%